(untitled) (Journal of Health, Population and Nutrition, 2011)
This pilot case-control study at a tertiary-care hospital over a four-month period was aimed at evaluating the possible usefulness of screening of TORCH (Toxoplasma gondii, rubella virus, cytomegalovirus, and Herpes simplex virus) in females with bad obstetric history. The study included 12 women with bad obstetric history and a similar number of matched controls with previous normal pregnancies. A serological evaluation of TORCH infections was carried out by detecting IgG and IgM antibodies against these infections by ELISA test-kit. Statistical analysis was not done to compare the results relating to the two groups due to a small number of cases and controls included in the study. Ten (83.3%) of the 12 cases with bad obstetric history and two (16.7%) of the 12 healthy controls were serologically positive at least for one of the TORCH agents. The seropositivity rate in women with bad obstetric history was quite high compared to that in the normal healthy controls. The results suggest that a previous history of pregnancy wastage and the serological evaluation of TORCH infections during current pregnancy must be considered while managing cases with bad obstetric history. Key words: Bad obstetric history; Case-control studies; TORCH screening; Nepal DOI: 10.3329/jhpn.v29i1.7569 J HEALTH POPUL NUTR 2011 Feb;29(1):77-80